An affair to remember - McCarey, Leo (Twentieth Century Fox Film Corporation, 1985)
In this poignant and humorous love story nominated for four Academy Awards, CARY GRANT and DEBORAH KERR meet on an ocean liner and fall deeply in love. Though each is engaged to someone else, they agree to meet six months later at the Empire State Building if they still feel the same may about each other. But a tragic accident prevents their rendezvous and the lover's future takes an emotional and uncertain turn.